The Resistance of Subaltern Class against Patriarchal Hegemony in Cantik Itu Luka by Eka Kurniawan - Ghefira Zahira Shofa; Imas Istiani (Journal of Language and Literature, 2025)
This study aims to examine patriarchal hegemony in the novel Cantik Itu Luka (Beauty Is a Wound) by Eka Kurniawan using the theories of Gramsci and Walby regarding colonial culture and ideology that controls the women who are classified as the subaltern classes under male power in various aspects of life. According to Spivak’s theory, subaltern class is an individual or social group that is marginalized under dominating power economically, socially, and culturally. This study also uses postcolonial approach by Tyson which serves to examine and respond to colonial influence on social structure, identity, and cultural continuity. The study of patriarchal hegemony in Cantik Itu Luka examines three main aspects: (1) the manifestation of patriarchal hegemony in the subaltern class; (2) the psychological and emotional impact of patriarchal hegemony on subaltern women; and (3) the forms of resistance against hegemonic. The research data are quotations from the novel contained in the form of words, phrases, sentences, and paragraphs that interpret the issue of patriarchal hegemony obtained from narration, dialog, characters' thoughts, and storyline. The data collection used literature study techniques, whereas the data analysis used qualitative descriptive techniques. The results of this study resulted in the discovery that patriarchal hegemony greatly influences society's ideology about subaltern women, all forms of community attitudes in the form of objectification, subordination, and marginalization of subalterns cause impacts, responses, and resistance by subaltern classes.